The Effect of Fermentation Time and Yeast Application on the Physical and Chemical Properties of Dry Cocoa Beans - Dinata, Ferry; Savitri, Dyah Ayu; Arum, Ayu Puspita; Kusbianto, Dwi Erwin (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Cocoa is a product with high economic potential throughout the world. Fermentation of cocoa beans is the most important process in processing cocoa beans, because at this stage the distinctive taste and aroma of chocolate will be formed in the cocoa beans. Getting quality dry cocoa beans requires extensive post-harvest handling. Therefore, it is hoped that this research can speed up the fermentation process while maintaining the quality of cocoa beans by adding NKL yeast to the process. This research was conducted using a Completely Randomized Design (CRD) using 2 factors. The first factor is fermentation time which consists of 3 levels, namely 2 days, 4 days and 6 days. Meanwhile, the second factor is yeast concentration which consists of 3 levels, namely 0%, 1% and 2%. The parameters measured include the number of seeds per 100 grams, cut test, fat content water content and temperature. The research results showed that interaction of the length of fermentation time with the concentration of yeast feeding had a significant effect on the variable number of seeds per 100 grams, and had a very significant effect on the variables of water content and fat content, while the effect was not significant on the cut test variable. The best combination of treatments was the combination of period of fermentation time (6 days) and yeast concentration of 2% (L3R3).